High negative predictive value diagnostic strategies for the reevaluation of early antifungal treatment: A multicenter prospective trial in patients at risk for invasive fungal infections. Issue 2 (August 2015) - Hasseine, Lilia; Cassaing, Sophie; Robert-Gangneux, Florence; Fillaux, Judith; Marty, Pierre; Gangneux, Jean-Pierre; The PF-qPCR Study Group, e
Summary Early antifungal therapeutic strategies are proposed during invasive fungal infection (IFI), but antifungal stewardship programs should institute a systematic reevaluation of prescriptions, particularly in the context of empirical treatment. Here, we aimed to evaluate the performances and particularly the negative predictive value (NPV) of diagnostic strategies, including a whole blood panfungal quantitative PCR assay (PF-qPCR) in a high risk population for IFI. The first step was to standardize and optimize a new PF-qPCR targeting ITS2 region. Then, this method was evaluated in a multicenter prospective study including 313 patients with suspected IFI for whom an early antifungal treatment was prescribed. All patients enrolled at day 0 of their treatment benefited from serum Aspergillus galactomannan (GM) antigen detection twice a week, weekly PF-qPCR assay, and when indicated and feasible, CT-scan and mycological sampling. In total, 125 of 313 patients were diagnosed with IFI: 68 invasive aspergillosis (eight proven, 48 probable and 12 possible), one fusariosis, 47 candidemia, three disseminated candidiasis and six cryptococcosis. Globally, the sensitivity of the PF-qPCR assay was only 40%, but the specificity, PPV and NPV were 96%, 88% and 69%, respectively. In the population of patients at high risk for invasive aspergillosis who also benefited from Aspergillus GM detection, the sensitivity and the NPV of the combined detection reached to 78% and 84%, respectively. Even higher NPV were obtained when combining negative PF-qPCR and CT scan (95%) as well as negative GM and CT scan (93%), thus allowing to rationalize and re-evaluate the prescription of empirical treatment in such highly selected population.